INTAKE GIZI MAKRO ATLET ANGKAT BERAT KALIMATAN BARAT MENUJU PEKAN OLAHRAGA NASIONAL XX - Ite Viani; Edi Purnomo; Uray Gustian (Universitas Tanjungpura, 2022)
The purpose of this study was to determine the adequacy of protein intake for weightlifters in preparation for the upcoming PON. Quantitative descriptive research, using survey method. The research instrument uses a table food recall and activity recall format. The research sample amounted to 5 athletes with a total sampling technique. The data analysis technique used descriptive statistics from food recall data which was calculated using nutrisurvey. The results of the study were the fulfillment of calories 37%, fulfillment of protein 67.8%, fulfillment of fat 41.6%, and fulfillment of carbohydrates 37.6%. These results indicate that the fulfillment of excessive protein intake, adequate amounts of fat and carbohydrate intake in deficiency of all the total energy needed.